Pemanfaatan Tablet BOS Afirmasi Peningkatan kompetensi guru dalam penggunaan media tablet bos afirmasi di SMA Negeri Kundur Kepulauan Riau - Memme Nini (JINoP (Jurnal Inovasi Pembelajaran), 2021)
This research was conducted at SMA Negeri 3 Kundur following the policy from the governor of Kepulauan Riau on March 16, 2020 about online teaching and learning activities. It was shown that most teachers only used What’s App due to their limited knowledge about online learning media and the capacity of their devices. This study aims to describe the use of BOS Tablets Afirmasi by teachers. Descriptive approach was employed with school action research through series of workshops. The data was collected through interviews, observation, and documentation. The obtained data was analyzed through Milles and Huberman technique consisting of data reduction, data display, and data verification. Results showed that teachers could Google Classroom after the workshops, in which online learning and daily assessment process ran more smoothly. Some teachers have also used Telegram and Zoom well where they were also taking online training through those applications.